Efficiency Analysis of State Goverments in the Malaysian Fiscal Federalism - Abd. Ghani, Judhiana; Grewal, Bhajan S.; Ahmed, Abdullahi D.; Mohamed Nor, Norashidah (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
By analyzing state governments’ efficiency in allocating fiscal resources, this study evalu-ates the efficiency of state public finances under the Malaysian fiscal federalism. This is reflected in the policies, strategies and decisions made to allocate public expenditure as this measurement would enable us to explain the institutional quality of the public sector in respect of the concept of regional competitiveness. In particular, states play important role in supporting the private sector and the market-based economy. The Data Envelopment Analy-sis (DEA) under the dynamic condition and Tobit panel data regression model are conducted on data for all the thirteen states in Malaysia from 1990 to 2009. The results of DEA reveal evidence that the current centralized fiscal federalism system has been unable to create a competitive environment among state governments, resulting in low levels of efficiency in the states. As an extension of the DEA, Tobit panel data regression model is needed to identify the factors that influence technical efficiency in Malaysia and the result showed evidence that fiscal decentralization had positive and significant influence on state efficiency level, but that further efficiency gains could have been realized with greater decentralization. Thus, this study supports the contention that fiscal decentralization provides incentive structures to support higher state efficiency levels. The findings echo the main argument of Market Preserving Federalism theory that states become more efficient if more power is devolved to them whilst ensuring that they spend within their fiscal capacity.